Enhancing Life Skills in Early Childhood Education: How Digital Puzzles Make It True? - Syarifah, Syarifah; Damayanti, Ranie (Akademika, 2025)
In the rapidly evolving digital age, building children's life skills through creative play has become a crucial and popular technique in early childhood education. As a result, we propose employing digital puzzles to encourage creative play in early childhood education. Playing creatively with a digital puzzle can significantly improve children's life skills. They must assemble puzzle pieces to create the desired image pattern. According to various research and publications, creative play with digital puzzles can promote life skills in early infancy. We specifically look at the challenges of doing a literature review on improving life skills in early childhood education. Life skills in literature are divided into four sections based on the following themes: (1) the new concept of early childhood education, (2) integrating life skills in early childhood education with play and media, (3) encouraging creative play through digital puzzles, and (4) digital puzzles for life skills in early childhood classrooms: a case study in Indonesia. The article introduces each of the four themes with a contemporary anecdote and then presents a literary consensus. The article concludes with changes to improve life skills in early childhood education through creative play and digital riddles. Digital puzzles, as a form of creative play, help young children build life skills that will make them happier and more resilient in the face of daily challenges. Young children can grow into adults capable of creatively overcoming daily problems.